Perancangan Key Performance Indicators dan Pembuatan Dashboard Proyek Tenaga Surya PT. X - Axel Jeremmy Lee; Iwan Halim Sahputra (Jurnal Titra, 2022)
PT. X started a business process to introduce solar power generation devices as an alternative energy source. Currently, Key Performance Indicators of PT. X was not designed according to the company's business model and values. The company also does not have a dashboard to monitor the performance of each department and its achievements. Companies find it difficult to monitor their performance. The purpose of this final project is to design Key Performance Indicators based on the company's business model, values, and quality objectives. Database is also needed to record and store supporting data for calculating Key Performance Indicators. Data and calculation results are visualized in a dashboard to make it easier for companies to monitor the performance of each department. With this dashboard, companies also get information and insights related to the performance of solar projects. Companies can take advantage of information and insights to formulate strategies so that companies can improve the achievement of the company's Key Performance Indicators better.